PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GUIDED TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 37 PEKANBARU - Asri Gusniawati; Eddy Noviana; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weakness of student’s learning result of social subject. It show from 33 student’s, 18 students (54,55%) have lower score, and it is only 15 student’s (45,45%) have average score 69,39. The KKM of this school is 77. According to that problem, the research by implementing cooperative learning model guided teaching. In cycle 1, the percentage of teachers activity in first meeting is adquate 58,33%. In second meeting, teachers activity significantly increased to 66,67% with good category. In cycle 2, first meeting was in good category 79,19% and second meeting indicated a very good category 87,5%. Meanwhile, the activity of student’s also improved. In cycle 1 indicated 57,17% in adequate category and in cycle 2 has increased up to 62,5% with good category. In cycle 2, first meeting, the activity of student’s has been increasing to 75% with good category and second meeting indicated very good category 87,5%. An average score of student’s learning result before implementation is 69,39. It increased to 77,42 in cycle 1, and 83,33 incycle 2. In classical completeness, cycle 1 and cycle 2 were achieved. In conclussion, implementation cooperative learning model guided teaching can improve student’s learning result of fourth grade students of SD Negeri 37 Pekanbaru in social subject.Key words: Cooperative model guided teaching, learning result of social subject